INTRODUCTION - Serafimovski, Todor (Geologica Macedonica, 2014)
The Geologica Macedonica is an official publication of the "Goce Delčev" University, Faculty of Natural and Technical Sciences, Štip, Republic of Macedonia. It is published a yearly. The journal publishes original scientific papers, short communications, reviews, professional and educational papers from all fields of Mining, Geology, Petrology, Mineralogy and Geochemistry....